TINGKAT KEPUASAN PELANGGAN TERHADAP LAYANAN AKPINDO (Studi Kasus Terhadap Mahasiswa Kepeminatan Kuliner) - Rudhi Achmadi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
The quality of service provided by Akpindo to its customers is one of the important aspects for the company's marketing. This will affect the sustainable competitiveness of the business as one of the famous vocational school in Indonesia to compete with others. This study discusses three important issues: a) expectations of the students on the performance of Akpindo in conducting the learning process. The level of satisfaction of the students on the performance of Akpindo, and c) what steps need to be done to meet the expectations of students in the learning process. The purpose of this study is to determine a). expectations of the students on the performance of Akpindo in in conducting the learning process b). the level of satisfaction of the students on the performance of Akpindo, and c) what steps need to be done to meet the expectations of the students. The method of analysis used in this research is the analysis of quadrant (quadrant analysis), whereas the data obtained from questionnaires to a sample, interview and observation. Based on the research results, it can be concluded that there is gap between the expectations of the students and the performance of Akpindo. It can be seen from the level of interest/ expectations by 43,25% while the value of contentment only amounted to 34,16%, the difference is 9,09%. In addition, management has not yet implemented some attributes that are considered to be factors that affect customers’ satisfaction, including the elements that are considered important, such as: equipment for practical class, arrangement of equipment for practical class, comfort of practical classroom, quick services, and capability to answer problems.Based on the conclusion, the author then gives advice namely: management on future occasions should further improve the quality of service in all aspects to the students due to the persistence of the gaps between expectations and satisfaction levels. The need to continue to get feedback from customers (students) or desire to know the expectations of the students and also the need to build a shared commitment throughout the human resources available for the provision of excellent service to the students. Thus, knowing the deficiency in the management and other services, this step also serves to maintain the satisfaction of students and also to enhance the corporate image.